Mga paru-parong rosas (Pink butterflies) (Outline Digital Films, 2007)
Of the gay persuasion. The film revolves around two women, who suffer the consequences of their respective husband's burning passion for each other, who in turn find love and security in each one's forbidden embrace. The men choose to leave the world of reality and build their own where their love reigns. Theirs is an ill-fated affair that is above human laws above their family's will and beyond society's standards.